Impact of Behavioral Bias, Price Volatility, and Market Capitalization on Cryptocurrency Purchase Decisions in Indonesia - Bagja Rahma Putra; Fitrina Lestari; Kharisma Kharisma (CAKRAWALA : Management Science Journal, 2025)
This study investigates how market capitalization, price volatility, and behavioral biases affect decisions to buy cryptocurrencies. Because of its decentralized structure and extreme volatility, the cryptocurrency market frequently affects investment choices through psychological elements, including loss aversion, overconfidence, and herd mentality. This study uses a quantitative methodology to analyze data from the nine most traded cryptocurrencies using independent t-tests, multiple linear regression, and simple linear regression. According to the study's findings, decisions to buy cryptocurrencies are significantly positively influenced by herd behavior and overconfidence, as shown by high volatility, but not significantly by loss aversion. Furthermore, it has been demonstrated that price volatility significantly affects herd behavior, meaning that investors are influenced to follow the majority lead when prices fluctuate significantly. However, the degree of herd behavior is not affected by market capitalization, suggesting that psychological elements like herd behavior are more impacted by general market conditions than by market capitalization size. These results highlight how crucial it is to comprehend the psychological aspects of cryptocurrency market decision-making, since doing so can offer a better understanding of investor behavior and the workings of this extremely unpredictable market.